In vitro phagocytic activity of blood and milk neutrophils against Saccharomyces cerevisiae in primiparous and multiparous Karan Fries crossbred cows throughout the dry period and lactation cycle - DANG, A K; MUKHERJEE, JOYDIP; CHAUDHURY, MANDIRA; PRASAD, SHIV; MOHANTY, A K; KAPILA, SUMAN; KAPILA, RAJEEV (The Indian Journal of Animal Sciences, 2014)
The differences between in vitro phagocytic activity (PA) of neutrophils isolated from first lactating i.e., primiparous (PP) and multiparous (MP) Karan Fries (Holstein Fresian × Tharparkar) cows, were studied. Blood and milk samples were collected from 12 PP and 12 MP cows during different days of production cycle (dry period and lactation). Blood total leukocyte counts (TLC) and milk somatic cell counts (SCC) were significantly lower in PP as compared to MP cows during all stages of production cycle. Blood TLC was significantly higher at calving and then decreased towards the end of lactation in both the groups. Milk SCC was highest in colostrums, decreased significantly around mid lactation and again increased towards the end of lactation. Phagocytic activity (PA) of blood neutrophils was significantly higher in PP as compared to MP cows. Suppression of PA around parturition was less and also restored earlier in PP as compared to MP cows. PA of colostrums was higher in MP as compared to PP cows; however, PA of milk neutrophils was always higher in PP as compared to MP cows throughout the lactation period. Less PA of neutrophils make the MP cows more prone to infections during the production cycle. Therefore, proper care and nutrition should be provided to them throughout the production cycle.